Faith is Confidence: The Implication of Psychosocial Components in Faith-Based Educational Programs on Expressive Communication Skills of Adult Learners. Issue 2 (3rd May 2016) - Lynch, Erin M.
ABSTRACT: Faith-based programs for adult learners have environmental factors that differentiate them from non-faith based programs, but explicit empirical studies evaluating the impact of the psychosocial factors have been lacking in the literature. This study comparatively examines the achievement level of expressive communication skills as measured through writing in general education development (GED) program participants who were adult learners in faith-based and non-faith based programs. The article will discuss the context of faith from the literature, impact of psychosocial environmental factors, and provide implications for curriculum design for faith-based academic programs while addressing the research question of whether faith-based GED programs have an impact on the achievement of expressive communication levels of students compared to non-faith-based GED programs.